PENGARUH DIGITALISASI TERHADAP KETIMPANGAN PENDAPATAN REGIONAL DI INDONESIA - Muhammad Raka Dias; Rusy Dina (Media Riset Ekonomi Pembangunan (MedREP), 2026)
This study aims to analyze the influence of digitalization as measured by the variables of digital accessibility and digital skills as well as macroeconomic control variables including Gross Regional Domestic Product per capita and the open unemployment rate, on regional income inequality. The data used in this study are secondary data obtained from the badan pusat statistic in 34 provinces in Indonesia during the period 2015–2024. with the panel data regression method and the Random Effect Model selection method. The results show that the digital accessibility variable has a negative and insignificant effect on the Gini index. Conversely, the digital skills variable has a negative and significant effect on regional income inequality, indicating that increasing the digital capacity of the community contributes to reducing economic inequality. Meanwhile, the variables of GRDP per capita and the open poverty rate were found to have a negative and insignificant effect on income inequality at the provincial level. Simultaneously, all independent variables in this research model have a significant effect on regional income inequality in Indonesia.